2017
DOI: 10.3329/cmoshmcj.v16i1.34978
|View full text |Cite
|
Sign up to set email alerts
|

High Density Lipoprotein Cholesterol (HDL-C) Status in Patient's of Acute ST–Elevation Myocardial Infarction (STEMI)

Abstract: Background : Decrease plasma High Density Lipoprotein Cholesterol (HDL-C) and increase triglyceride are major dyslipidemia in our country due to effects of carbohydrate rich diet. The relationship of low level of HDL -C in patient's of AMI and its extents of severity in coronary artery disease will be very important for future management as well as prevention of Coronary Artery Disease (CAD). Objective : The aim of this study is to assess the level of serum HDL-C in AMI patient and to assess whether low serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…10% of study subjects had unstable angina which showed a similar distribution like a study done in Bangladesh. 23 The study showed that all the study subjects with abnormal HDL-C level have abnormal LDL-C level, abnormal CRP level, and abnormal LDL/HDL ratio. Inverse relationship between HDL and other lipids like LDL was evident in the study which was similar to other studies.…”
Section: Discussionmentioning
confidence: 90%
“…10% of study subjects had unstable angina which showed a similar distribution like a study done in Bangladesh. 23 The study showed that all the study subjects with abnormal HDL-C level have abnormal LDL-C level, abnormal CRP level, and abnormal LDL/HDL ratio. Inverse relationship between HDL and other lipids like LDL was evident in the study which was similar to other studies.…”
Section: Discussionmentioning
confidence: 90%